Depression in Sardinian immigrants in Argentina and residents in Sardinia at the time of the Argentinian default (2001) and the Great Recession in Italy (2015). Issue 1 (December 2017) - Carta, Mauro; Atzeni, Michela; D'Oca, Silvia; Perra, Alessandra; D'Aloja, Ernesto; Brasesco, Maria; Moro, Maria; Minerba, Luigi; Sancassiani, Federica; Moro, Daniela; Mausel, Gustavo; Bhugra, Dinesh
Abstract Background The aim of this study is to measure in two samples of Sardinian immigrants in Buenos Aires and representatives of the population in Sardinia the prevalence of depressive symptoms at the time of an economic crisis in Sardinia and to compare these results with those collected at the time of a similar crisis in Argentina more than 10 years before. Methods Observational study. The associations of Sardinian immigrants in Buenos Aires provided the lists of families of Sardinian origin. A random sample of one fifth of registered families was selected. The sample of a study carried out in Sardinia was used as the control. The results were compared with those of the previous study performed in 2001–2002. The Patient Health Questionnaire (PHQ9) was used for the screening of depression. Results The Sardinian immigrants show a lower rate of scoring positively on PHQ9 (i.e. less risk of being depressed) and reach statistical significance after standardization (8.7% vs. 13.1%, P  = 0.046). Young women (≤40) are at higher risk. On the contrary, the risk of depression was higher in Sardinian immigrants in Argentina during the 2001–2002 crises. Conclusion The study indicates a risk for depressive episodes linked to the fallout of the economic crisis (in Argentina in 2001–2002, in Sardinia in 2015) and specifically more in females than in males. Due to the associated socio-demographic risk factors, these results could be interpreted as due to an increase in non-bipolar depression.